Molecular characterization of Toxoplasma gondii and Sarcocystis spp. in raw kibbeh and other meat samples commercialized in Botucatu, Southeastern Brazil - Langoni, Helio [UNESP]; Generoso, Diego [UNESP]; Hayasaka, Ênio Yoshinori [UNESP]; Mantovan, Karine Bott [UNESP]; Menozzi, Benedito Donizete [UNESP]; Richini-pereira, Virgínia Bodelão; Silva, Rodrigo Costa Da (Colégio Brasileiro de Parasitologia Veterinária, 2021)
Toxoplasmosis occurs worldwide causing economic losses to the animal production and problems to the public health. The study aimed to detect Toxoplasma gondii and Sarcocystis spp.in 141 meat products from commercial meat cuts of pork, beef, and kibbeh sold in commercial markets from Botucatu, SP, Brazil. Samples were bioassayed in mice to isolate the parasite, and the parasite DNA detected by PCR targeting the 529 base pairs repeat element region (PCR-529-bp). All samples resulted negative on bioassay, whereas PCR positive for 9 (6,38%), distributed as 5/48 beef, 3/49 pork, and 1/44 kibbeh. PCR-positive were investigated for the the parasite genotype using multiplex-, nested-, and RFLP-PCR for 11 markers (SAG1, 5’-3’SAG2, alt.SAG2, SAG3, B-TUB, GRA6, L358, c22-8, c29-6, PK1, Apico). Complete genotype was determined on just one PCR-positive sample that matched MAS, TgCkBr89 and TgCkBr147 isolates already identified. In addition, nested- and RFLP-PCR targeting 18S rRNA was run for all PCR-positive samples and, the products, sequenced and aligned to the GenBank at NCBI website. Four samples showed 100% homology with T. gondii (GenBank #L37415.1), three with Sarcocystis hominis (GenBank #AF006471.1), two Sarcocystis cruzi (GenBank #AF176934.1), and one Sarcocystis hirsuta (GenBank #AF006469.1), indicating the circulation of T. gondii and Sarcocystis spp.

A toxoplasmose está mundialmente distribuída e causa perdas na produção animal e problemas de saúde pública. Objetivou-se detectar Toxoplasma gondii e Sarcocystis spp. em 141 produtos cárneos de origem suína (49), bovina (48) e de quibe cru (44), comercializados em mercados de Botucatu, SP, Brazil. Realizou-se bioensaio das amostras em camundongos para isolamento do parasita, e detecção do DNA pela reação em cadeia pela polimerase, tendo como alvo a região do elemento repetitivo de 529 pares de bases (PCR-529-bp). Todas as amostras foram negativas ao bioensaio e 9 (6,38%) positivas à PCR, sendo 5/48 bovinas, 3/49 suínas e 1/44 quibe. Determinou-se a genotipagem das amostras positivas pela multiplex-, nested- e RFLP-PCR com 11 marcadores (SAG1, 5’-3’SAG2, alt.SAG2, SAG3, B-TUB, GRA6, L358, c22-8, c29-6, PK1, Apico). Obteve-se genótipo completo em uma amostra, semelhante a outros já identificados (MAS, TgCkBr89 e TgCkBr147). Nested- e RFLP-PCR do gene 18S rRNA das amostras positivas à PCR foram realizadas, e os produtos da nested-PCR, sequenciados e alinhados com dados do GenBank no NCBI. Quatro apresentaram 100% de homologia com T. gondii (L37415.1), duas Sarcocystis hominis (AF006471.1), duas Sarcocystis cruzi (AF176934.1), uma Sarcocystis hirsuta (AF006469.1), indicando a circulação de T. gondii e Sarcocystis spp.
Caracterização molecular de Toxoplasma gondii e Sarcocystis spp. em amostras de quibe cru e de outras carnes comercializadas em Botucatu, Região Sudeste do Brasil
Keywords: Toxoplasmosis; sarcocystosis; meat products; food safety; public health; molecular techniques; Toxoplasmose; sarcocistose; produtos cárneos; segurança alimentar; saúde pública; técnicas moleculares